Poxviruses: smallpox (variola), vaccinia and monkeypox - Traktman, Paula (Henry Stewart Talks, 2007)
Poxvirus life cycle: chromosome structure, virion structure and virion entry, Viral proteins needed for entry and mechanism of entry of EV (enveloped virion), Gene expression of EV: early transcription, intermediate and late transcription, Working model of Poxvirus genome replication, Morphogenesis of EV, Key features of the IV to MV (mature virions) transition, Poxviruses encode a three-protein complex that generates disulfide bonds in the cytoplasm, Formation of EEV (extracellular enveloped virions) and EV mediators of cell-to-cell and distal spread, Poxviruses encode a large array of immunomodulators, Models for the study of Poxvirus pathogenesis, Smallpox (Variola virus) and smallpox disease, Pathogenicity of Variola virus vs. Vaccinia virus, Official declaration of the eradication of smallpox, Monkeypox virus, Antiviral therapy and new vaccines for Poxviruses
Archived at 2017/12/31